OBESITY IN TEMPLE SYNDROME - Teoh, Siu Yin; Selveindran, Nalini M; Hong, Janet YH; Morthy, Sasirekha K; Ong, Jayne AX (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Temple syndrome is a rare imprinting disorder caused by a maternal uniparental disomy of chromosome, paternal deletion of 14q32 or isolated methylation defect of the MEG3-DMR. Review of the electronic medical records with salient clinical and investigations recorded. CASE MKA is an 8 years and 5 months old male who presented with central hypotonia with poor sucking at birth. He was delivered term at 2.62 kg. Antenatally, the mother had oligohydramnios. During clinic follow-up, MKA remained well but he remained obese with a BMI of more than 97th centile. He looked dysmorphic with plagiocephaly, narrow bifrontal diameter, almond-shaped eyes, downturned mouth, thin upper lip, thick earlobes, small hands and feet, left single palmar crease, pes planus and genu valgus. Neurological examination revealed central hypotonia. He had failure to thrive during infancy where he was on orogastric feeding for 1 month, achieved brief normalisation at 1 year old, followed by hyperphagia and rapid weight gain since the age of 2 years old. He is a product of a nonconsanguineous marriage. He also has isolated central hypothyroidism with left cerebral hemiatrophy. Chromosomal study showed 46XY karyotype. A series of imaging including abdominal ultrasound, KUB, pelvis, cranium, echocardiogram and brain MRI - was normal. He was suspected to have Prader Willi Syndrome, but methylation test was normal. Genetics team co-managed and treated him for Temple Syndrome with maternal uniparental disomy 14 with Prader Willi Syndrome like phenotype. CONCLUSION Temple syndrome is largely manifested by physical defects necessitating obligatory supportive therapies early in the life of affected individuals. The syndrome has shown that a subset of patients develop obesity. BMIs increased along the reference curves in most patients. Endocrine anomalies are prevalent, with truncal obesity developing as early as 4 to 6 years.